A compact all fiber refractive index sensor based on modal interference - Wo, Jianghai (2013)
In this paper, we propose and experimentally demonstrate a compact all fiber refractometer based on fiber modal interference. Different from other published program mostly based on the interference between high order modes in the Multi-mode fiber (MMF), we use the interference between core and cladding modes in the Single-mode fiber (SMF). The sensing head can be simply fabricated by splicing a section of SMF between two MMFs. Due to the different cladding modes' contribution into the interference, the transmission spectrum dips with specific interference order shifts differently with the changes of the environmental parameters. The sensor shows good response to the refractive index (RI) variation with the highest sensitivity of -96.85nm/RIU (refractive index unit).